Application of Legal Customs in Lithuania in 1918–1940 - Machovenko, Jevgenij (Teisė, 2022)
This article determines, based on legal norms, case law, and the scientific doctrine, the significance of legal customs in Lithuania in 1918–1940: it describes the legal customs in the status quo res erant ante bellum, i.e., in relation to which social groups and to what extent were the customs applied in Lithuania under the law of the Russian Empire. The significance of the constitutional provision on the reception of pre-war law for legal customs is revealed. The paper also describes the policy of the legislator with regard to legal customs, the limits of the application of customs by law, and the tendencies of legislation in this regard.